Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3389/fcell.2021.719072
|View full text |Cite
|
Sign up to set email alerts
|

Next Generation Microbiome Research: Identification of Keystone Species in the Metabolic Regulation of Host-Gut Microbiota Interplay

Abstract: The community of the diverse microorganisms residing in the gastrointestinal tract, known as the gut microbiota, is exceedingly being studied for its impact on health and disease. This community plays a major role in nutrient metabolism, maintenance of the intestinal epithelial barrier but also in local and systemic immunomodulation. A dysbiosis of the gut microbiota, characterized by an unbalanced microbial ecology, often leads to a loss of essential functions that may be associated with proinflammatory condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 163 publications
(226 reference statements)
1
14
0
Order By: Relevance
“…Based on the ranking of the median structural keystoneness, we found that among those top-ranking species, many of them have been identified as keystone species that carry unique functions and are essential for the maintaining host-microbe hemeostasis 41 . For example, Bifidobacteria are keystone microorganisms in gut microbiota associated with early life 42 ;…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the ranking of the median structural keystoneness, we found that among those top-ranking species, many of them have been identified as keystone species that carry unique functions and are essential for the maintaining host-microbe hemeostasis 41 . For example, Bifidobacteria are keystone microorganisms in gut microbiota associated with early life 42 ;…”
Section: Resultsmentioning
confidence: 99%
“…Prevotella copri is a keystone species of a healthy human intestinal mucosa 43 ; Faecalibacterium prausnitzii is a keystone species that produces butyrate and its reduced abundance has been associated with Crohn's disease 44 ; Bifidobacterium longum is a minority species, but influences gut microbiota formation by breaking down complex carbohydrates and providing degradants for other bacterial groups to use 45 ; Ruminococcus bromii plays key roles in promoting the synergistic utilization of resistant starch (RS) by initiating degradation of insoluble RS particles 5,41 (Fig. 5a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The so-called gut microbiome includes the whole genome of the GM, encoding for over 100-fold more genes than the human genome ( 36 ). The recent advent of metagenomics, which combines the next-generation sequencing (NGS) technology with the computational analysis of the 16S ribosomal RNA (rRNA) amplicons, helps in the characterization of both diversity and abundance of the gut microbiome ( 37 ). Metagenomics, together with metatranscriptomics, metaproteomics, and metabolomics, is currently allowing us to understand the impact of each individual bacterial species on the health of the host ( 38 ).…”
Section: Features Of Gut Microbiotamentioning
confidence: 99%
“…The importance of AhR cannot be overemphasized as it plays a crucial role in barrier integrity; intestinal and immune homeostasis, mostly due to the regulation of tight junction proteins; the generation and survival of intraepithelial lymphocytes (IELs); the production of IL-22 and IL-10; the regulation of peristalsis and microbiota density; the regulation of goblet cell differentiation in the colon, specifically preventing goblet cell depletion in the elderly [ 2 , 122 , 127 , 137 ]; and the stimulation of antimicrobial peptide production via IL-22 [ 138 , 139 , 140 , 141 , 142 ]. Individuals with IBD and celiac disease have low levels of AhR in their feces [ 133 ].…”
Section: Interkingdom Communicationmentioning
confidence: 99%